Information technology and it place in today's legal practice, research and administration of justice / Yusuf Ibrahim Arowosaiye - Arowosaiye, Yusuf Ibrahim (2014)
The growth recorded a few decades ago in the development of ICTs had a fundamental impact on the legal practice, legal education and administration of justice in various countries of the world. This development has indeed increased the pace of world economic cum political activities. The development is also transforming the traditional legal practice landscape. IT infrastructure and tools offer bundles of opportunities for advancing quality of legal service delivery and effective administration of justice. ICTs has changed the entire global legal practice landscape and law firms, regardless of their size must be fully ready to migrate into the virtual legal community and take advantage of the opportunities offered by the digital revolution. Against the above backdrop, this paper synthesizes the inevitable paradigm shift which ICTs has foisted on legal practice, legal education and administration of justice. The discourse examines the response of the legal profession to this development and identifies the challenges it poses as a result of IT integration in legal practices and administration of justice. The discourse formulates the thesis and provides empirical evidence to establish that legal practice and administration of justice are experiencing positive development in the information technology age. It also addresses the concern of one of the extreme schools of thought which interprets these changes as being symptomatic of the decline of the legal profession. The paper concludes by advocating for total embrace of digital technology in contemporary legal practice, legal education and administration of justice. The methodology employed in evaluating the impact of IT on legal practice, legal education and administrations of justice are analytical and critical approaches. The paper offers a general conclusion on the challenges of integration of ICTs in today's legal practice and administration of justice and proffers pragmatic recommendations on the future of legal practice in the information age.